2022
DOI: 10.1021/acs.macromol.2c00669
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Effects of Hydrogen Bonds and Molecular Weights on the Phase and Crystallization Behaviors of Binary Block Copolymers

Abstract: We investigated the competitive effects of the hydrogen-bonding interaction and molecular weight on the phase and crystallization behaviors of polystyrene-block-poly(ethylene oxide) (PS-b-PEO)/polystyrene-block-poly(acrylic acid) (PS-b-PAA) blends. The hydrogen-bonding interaction between PEO and PAA chains improved their miscibility, enabling the distinct block copolymers to co-organize into common PS and PEO/PAA microdomains. When the molecular weight ratio of PS-b-PEO to PS-b-PAA exceeded 4.5, the entropy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…We only used PS- b -PEO whose molecular weight was comparable to or slightly higher than the molecular weight of PS- b -PAA. When the molecular weight of PS- b -PEO was considerably higher than that of PS- b -PAA, the organization of long PEO chains into coexisting PEO/PAA microdomains caused entropy penalty, resulting in macrophase separation . Similar to the SAXS patterns of PS 96 - b -PEO 261 /PS- b -PAA blends, those of PS 207 - b -PEO 455 and its blend with 20 wt % PS- b -PAA exhibited a preferentially oriented microdomain morphology, which was verified by the arc feature along the z⃗ direction when the patterns were recorded using the X-ray beam through the y⃗ direction (Figure a,b).…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…We only used PS- b -PEO whose molecular weight was comparable to or slightly higher than the molecular weight of PS- b -PAA. When the molecular weight of PS- b -PEO was considerably higher than that of PS- b -PAA, the organization of long PEO chains into coexisting PEO/PAA microdomains caused entropy penalty, resulting in macrophase separation . Similar to the SAXS patterns of PS 96 - b -PEO 261 /PS- b -PAA blends, those of PS 207 - b -PEO 455 and its blend with 20 wt % PS- b -PAA exhibited a preferentially oriented microdomain morphology, which was verified by the arc feature along the z⃗ direction when the patterns were recorded using the X-ray beam through the y⃗ direction (Figure a,b).…”
Section: Resultsmentioning
confidence: 66%
“…However, the hydrogen bonds hampered PEO crystallization, causing substantial decreases in the crystallization kinetics and crystallinity of PEO. Although previous studies have demonstrated the crystallization behavior of binary block copolymers, ,, crystal orientation in binary block copolymers remains unclear. In the present study, we varied the molecular weight of PS- b -PEO but not that of PS- b -PAA to investigate the crystal orientation of PEO in the resulting microdomain morphologies.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A study investigated the crystallization in symmetric block copolymer mixtures comprising polystyrene- block -poly(ethylene oxide) (PS–PEO)/polystyrene- block -poly(acrylic acid) (PS–PAA) blends. 17 In these blends, only PEO molecules were crystallizable and PAA hydrogen bonded with PEO, hindering PEO crystallization. Because PEO and PAA were co-organized into coexisting PEO/PAA microdomains, PEO crystallization was strongly affected by the molecular weight ratio of PEO to PAA.…”
Section: Introductionmentioning
confidence: 99%
“…13 In contrast to chemically identical block copolymer mixtures, chemically unidentical binary block copolymer mixtures demonstrate microphase separation when the blends are endowed with specific molecular interaction. 9, [14][15][16][17] For instance, in a mixture of (A-B) a and (A-C) b block copolymers in the presence of a hydrogen-bonding interaction between the B and C block chains, the hydrogen-bonding interaction facilitates coordering of the B and C block chains in a coexisting microdomain, which then results in the formation of a microphaseseparated morphology. 17 Furthermore, hydrogen bonds reverse the phase behavior of each block copolymer in the blend that exhibits an upper-critical-ordering-transition-type interaction parameter to a lower-critical-ordering-transition-type phase diagram.…”
Section: Introductionmentioning
confidence: 99%